2011
DOI: 10.1074/jbc.m111.236737
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Factor 4 (KLF4) Activates the Transcription of the Gene for the Platelet Isoform of Phosphofructokinase (PFKP) in Breast Cancer

Abstract: Krü ppel-like factor 4 (KLF4) is a transcription factor that plays an important role in cell differentiation, proliferation, and survival, especially in the context of cancers. This study revealed that KLF4 activates glycolytic metabolism in breast cancer cells by up-regulating the platelet isoform of phosphofructokinase (PFKP). KLF4 activated the transcription of the PFKP gene by directly binding to the PFKP promoter. Whereas glucose uptake and lactate production were inhibited by the knockdown of KLF4, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 24 publications
5
76
1
2
Order By: Relevance
“…The fact that KLF4 overexpression resulted in worse survival has been demonstrated by many clinical data, and the reason has been widely discussed. Some recent studies suggested that KLF4 participates in many signaling pathways that support multiple aggressive traits in breast cancer, such as maintenance of high glycolytic metabolism27 and upregulation of Notch signaling 11,28. The present study indicates that high KLF4 expression leads to a worse outcome possibly due to resistance of chemotherapy.…”
Section: Discussionsupporting
confidence: 52%
“…The fact that KLF4 overexpression resulted in worse survival has been demonstrated by many clinical data, and the reason has been widely discussed. Some recent studies suggested that KLF4 participates in many signaling pathways that support multiple aggressive traits in breast cancer, such as maintenance of high glycolytic metabolism27 and upregulation of Notch signaling 11,28. The present study indicates that high KLF4 expression leads to a worse outcome possibly due to resistance of chemotherapy.…”
Section: Discussionsupporting
confidence: 52%
“…In these studies it was demonstrated that in breast cancer cells, KLF4 activates the transcription of the PFK-P gene directly by binding to its promoter [19]. To investigate the expression of the PFK gene in our system we performed qRT-PCR analysis in two different breast cancer lines in sorted differentiated cells (ZsGreen-cODC-neg) and sorted BCSCs (ZsGreen-cODC-pos).…”
Section: Resultsmentioning
confidence: 99%
“…Glyceraldehyde-3-phosphate dehydrogenase, decreased in ADP induced activation, was shown to be required for the transport of nitric oxide in platelets [49]. ATP-dependent 6-phosphofructokinase platelet type, also found to be less abundant in ADP induced PMPs, was shown to play a critical role in cell proliferation in breast cancer cells [50]. A small group Fig.…”
Section: Discussionmentioning
confidence: 97%